Selective Degradation and Quantification of Nucleoporins in the Nuclear Pore by Auxin‐Inducible Degrons and Single‐Molecule Microscopy. Issue 9 (5th September 2022) - Tingey, Mark; Li, Yichen; Yang, Weidong
Abstract: There is a significant current question regarding the viable copy numbers of nucleoporins required for the function of the nuclear pore complex (NPC) in eukaryotic cells. The NPC consists of approximately 30 different nucleoporins in an eight‐fold symmetry, meaning that there are multiple duplicates of each nucleoporin present within the nuclear pore. We recently developed a method that combines auxin‐inducible degrons and single‐molecule super‐resolution microscopy to evaluate the copy number of nuclear basket nucleoporins required for the successful function of the NPC. Here, we describe the theory behind this auxin‐inducible degron and single‐molecule super‐resolution microscopy method, and we detail a step‐by‐step process to selectively degrade nucleoporins either completely or in a stepwise manner. © 2022 Wiley Periodicals LLC. Basic Protocol 1 : Degradation of target nucleoporins Basic Protocol 2 : Quantification of nucleoporin copy number via narrow‐field fluorescence microscopy